Impact of Oil Price Volatility on Selected Sectors of the Polish Stock Market - Karol WOJTOWICZ; Konrad SZYDŁOWSKI (Communications of International Proceedings, 2024)
The commodity market has a significant impact on the global economy. Crude oil is one of the most important energy commodities, used to produce gasoline, diesel fuel, jet fuel and many other products. Changes in oil prices can have several different economic effects, by affecting inflation, trade balance, exchange rate, and many other macro- and micro-economic indicators. The main aim of the research is to identify the impact of oil prices on the Polish capital market. The co-movement of WTI Brent returns in relation to the sector indices of the Warsaw Stock Exchange was examined. The oil price impact assessment considers the period from 2014 to 2023. The research shows that out of fourteen indices, a significant relationship was observed in the case of four sectors: WIG Banks, WIG Chemicals, WIG Mining and WIG Fuel. In the case of most of the remaining indices, the correlation coefficients were positive but low.
Keywords: WTI Brant; commodity; stock market; indices